Equality beyond debate John Dewey's pragmatic idea of democracy - Jackson, Jeff 1986- (Cambridge University Press, 2018)
While many current analyses of democracy focus on creating a more civil, respectful debate among competing political viewpoints, this study argues that the existence of structural social inequality requires us to go beyond the realm of political debate. Challenging prominent contemporary theories of democracy, the author draws on John Dewey to bring the work of combating social inequality into the forefront of democratic thought. Dewey's 'pragmatic' principles are deployed to present democracy as a developing concept constantly confronting unique conditions obstructing its growth. Under structurally unequal social conditions, democracy is thereby seen as demanding the overcoming of this inequality; this inequality corrupts even well-organized forums of political debate, and prevents individuals from governing their everyday lives. Dewey's approach shows that the process of fighting social inequality is uniquely democratic, and he avoids current democratic theory's tendency to abstract from this inequality
Keywords: Dewey, John / 1859-1952 / Political and social views; Democracy / Social aspects; Equality; Dewey, John / 1859-1952; Political and social views